The Exegesis of Ṭaharah Verses in Al-Ṭahawi’s Tafsir Aḥkam al-Qur’an - Zahrotul Kamilah; Sakila Lu’Luil Maknun (Journal of Islamic Thought and Contemporary Studies, 2025)
Aḥkam Tafsir refers to the interpretation of Qur'anic verses related to Islamic law, playing a crucial role in shaping the understanding of legal principles and practices among Muslims. Historical figures such as Al-ṭaḥawi have contributed significantly with their works, including Aḥkam al-Qur'an, which explains the foundational principles of Islamic jurisprudence (fiqh) in the Qur'an, particularly regarding the concept of ṭaharah (purification). The discussion of ṭaharah verses in this context aims to uncover new perspectives from Al-ṭaḥawi's interpretation in Aḥkam al-Qur'an. This study employs a library research method, focusing on the book Aḥkam al-Qur'an as the secondary object of research. The findings from the analysis of Aḥkam al-Qur'an by Abu Ja'far Al-ṭaḥawian expert in hadith and fiqh reveal that the ṭaharah verses are interpreted in a detailed manner, supported by clear sources and the opinions of other scholars.